Degradação de reservas bioquímicas e hormonais durante a germinação in vitro de sementes imaturas e poliaminas associadas ou não ao picloram na embriogênese somática de Euterpe edulis martius - Costa, Joana Silva (2023)
Euterpe edulis Martius, popularly known as juçara, belongs to the Arecaceae family, is native to the Atlantic Forest, and is included in the Brazilian List of Endangered Species. This species is single-stemmed, has propagation exclusively by seeds, recalcitrant seeds and slow germination, factors that lead to the risk of extinction due to the characteristics of the source of propagule and palm heart harvest, and justify the search for alternative methods of propagation. Therefore, knowledge about the morphological, physiological and biochemical changes that this species undergoes throughout its germination process is very important, as well as somatic embryogenesis that appears in this scenario as a viable option, enabling the generation of numerous plants from just an explant. Chapter 1 portrays the degradation of juçara seed reserves during germination (0, 10, 20, 30, 40, 60, 120, 180 days after germination), in which morphophysiological and biochemical analyzes were submitted. It was observed in this experiment that, while the dry mass of the seeds was reduced, there was an increase in the morphological variables of the seedlings. All reserves were degraded over the period under analysis, however, proteins were metabolized and consumed before carbohydrates, starches and lipids, indicating the importance of the first reserve cited in germination and subsequent ones in seedling growth. Other reserves such as fibers and lignin are closely related to the acquisition of mechanical strength by seedling structures. Even during the post-germination period, the hormones zeatin, indoleacetic acid, and abscisic acid were detected, which are related to the start of germination, and with inhibitory effects, such as zeatin on abscisic acid in the regulation of dormancy. It was also observed the hormonal precursor 1-aminocyclopropane-1-carboxylic acid, which is also related to germination, the polyamines (spermine, spermidine x and putrescine), which are linked to the development of the embryo, and the amino acid proline, which works as an inhibitor of germination. In summary, the increase in the average values of the efficiency of use of reserves that occurs together with the decrease in the dry mass of the seeds, affirm that the endospermic reserves are translocated to the vegetative axis, and promote the germination and the growth of the seedlings of E. edulis. In addition, haustorial atrophy signals the end of the degradation period of these reserves, which is marked by a significant increase in moisture and a reduction in seed dry mass. Chapter 2 depicts the induction and maturation of somatic embryogenesis of stem segments of E. edulis, whose treatments were different concentrations of spermine or spermidine (0, 50, 100 and 150 μM) combined or not with picloram (150 μM), and the polyamines were subdivided into two experiments. Spermidine (150 μM) showed the highest number of somatic embryos, a larger zone of embryo formation, in addition to intense procambial and meristematic formation, evidencing the requirement of this polyamine during the histodifferentiation of somatic embryos of E. edulis. Finally, the somatic globular embryos (emblings) formed presented asynchronous development, and the presence or absence of basal cells of the globose body, resembling the zygotic embryo suspensor, which refers to its variable origin (uni or multicellular).